Acute Limb Ischemia in Peripheral Artery Disease: Insights From EUCLID. Issue 7 (13th August 2019) - Hess, Connie N.; Huang, Zhen; Patel, Manesh R.; Baumgartner, Iris; Berger, Jeffrey S.; Blomster, Juuso I.; Fowkes, F. Gerry R.; Held, Peter; Jones, W. Schuyler; Katona, Brian; Mahaffey, Kenneth W.; Norgren, Lars; et al.
Abstract : Background: Acute limb ischemia (ALI) is an important clinical event and an emerging cardiovascular clinical trial outcome. Risk factors for and outcomes after ALI have not been fully evaluated. Methods: EUCLID (Examining Use of Ticagrelor in Peripheral Artery Disease) randomized patients with peripheral artery disease to ticagrelor versus clopidogrel. Enrollment criteria included an ankle-brachial index ⩽0.80 or previous lower extremity revascularization. Patients were grouped according to the primary outcome, postrandomization ALI hospitalization. Baseline factors associated with ALI were identified using Cox proportional hazards modeling. Models with ALI hospitalization as a time-dependent covariate were developed for secondary outcomes of major adverse cardiovascular events (myocardial infarction, cardiovascular death, ischemic stroke), all-cause mortality, and major amputation. Results: Among 13 885 patients, 1.7% (n=232) had 293 ALI hospitalizations (0.8 per 100 patient-years). Patients with versus without ALI were younger and more often had previous peripheral revascularization and lower baseline ankle-brachial index. Treatment during ALI hospitalization included endovascular revascularization (39.2%, n=115), surgical bypass (24.6%, n=72), and major amputation (13.0%, n=38). After multivariable adjustment, any previous peripheral revascularization (Hazard Ratio [HR] 4.7, 95% CI 3.3–6.8, P <0.01), baseline atrial fibrillation (HR 1.8, 95% CI 1.1–3.2, P =0.03), and baseline ankle-brachial index ⩽0.60 (HR 1.3 per 0.10 decrease, 95% CI 1.1–1.5, P <0.01) were associated with higher ALI risk. Older age (HR 0.8 per 10-year increase, 95% CI 0.7–1.0, P =0.02) and baseline statin use (HR 0.7, 95% CI 0.5–0.9, P <0.01) were associated with lower risk for ALI. There was no relationship between randomized treatment to ticagrelor or clopidogrel and ALI. Among patients with previous revascularization, surgical versus endovascular procedures performed more than 6 months prior were associated with ALI (adjusted HR 2.63, 95% CI 1.75–3.96). In the overall population, ALI hospitalization was associated with subsequent MACE (adjusted HR 1.4, 95% CI 1.0–2.1, P =0.04), all-cause mortality (adjusted HR 3.3, 95% CI 2.4–4.6, P <0.01), and major amputation (adjusted HR 34.2, 95% CI 9.7–20.8, P <0.01). Conclusions: Previous peripheral revascularization, baseline atrial fibrillation, and lower ankle-brachial index identify peripheral artery disease patients at heightened risk for ALI, an event associated with subsequent cardiovascular and limb-related morbidity and mortality. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01732822. Abstract : Supplemental Digital Content is available in the text.